IMPLEMENTASI KEBIJAKAN PERLINDUNGAN ANAK TERLANTAR PADA DINAS SOSIAL KOTA JAYAPURA - Gombo, Atius; Aedah, Nur; Tebay, Vince (JURNAL KEBIJAKAN PUBLIK, 2023)
This study aims to analyse and describe the Implementation of the Protection of Neglected Children Policy at the Jayapura City Social Service, as well as to analyse the Supporting and Obstacle Factors. This research is important because the protection of neglected children is a state responsibility that must be immediately implemented effectively to prevent wider social impacts and protect children's basic rights in accordance with the mandate of Law Number 35 of 2014. The approach used in this research is descriptive qualitative with data collection methods are observation, documentation, and interviews. The data that has been collected is presented by reducing data that is not needed in the research. After that, conclusion drawing and verification were carried out. The results of this study indicate that the Implementation of the Protection of Neglected Children Policy at the Jayapura City Social Service, based on Edward III Theory that from the aspect of communication, the delivery of information is less clear. Resources, the availability of human resources in handling the protection of abandoned children is lacking. Disposition, in employee recruitment most of the civil servants. Bureaucratic Structure, the absence of SOPs results in no uniformity of the implementers. Supporting and Inhibiting Factors for the Implementation of Neglected Children Protection Policies at the Jayapura City Social Service are Supporting Factors, the lack of a halfway house to accommodate neglected children is a very important factor in alleviating children's problems in Jayapura City. Inhibiting Factors, the poor and neglected children who are cared for by the state are not just a discourse, because the government has not optimally handled them.